Safety of clonidine used for long‐term sedation in paediatric intensive care: A systematic review. Issue 3 (23rd December 2020) - Eberl, Sonja; Ahne, Gabriele; Toni, Irmgard; Standing, Joseph; Neubert, Antje
Abstract : Aim: Although not approved, the α‐adrenoceptor agonist clonidine is considered an option for long‐term sedation protocols in paediatric intensive care. We reviewed adverse effects of clonidine occurring in this indication. Methods: Relevant literature was systematically identified from PubMed and Embase. We included interventional and observational studies on paediatric patients admitted to intensive care units and systemically long‐term sedated with clonidine‐containing regimes. In duplicates, we conducted standardised and independent full‐text assessment and extraction of safety data. Results: Data from 11 studies with 909 patients were analysed. The studies were heterogeneous regarding patient characteristics (age groups, comorbidity, or comedication) and sedation regimes (dosage, route, duration, or concomitant sedatives). Just four randomised controlled trials (RCTs) and one observational study had comparison groups, using placebo or midazolam. For safety outcomes, our validity evaluation showed low risk of bias only in three studies. All studies focused on haemodynamic problems, particularly bradycardia and hypotension. Observed incidences or subsequent interventions never caused concerns. However, only two RCTs allowed meaningful comparisons with control groups. Odds ratios showed no significant difference between the groups, but small sample sizes (50 and 125 patients) must be considered; pooled analyses were not reasonable. Conclusion: All evaluated studies concluded that the use of clonidine in paediatric intensive care units is safe. However, a valid characterisation of the safety profile remains challenging due to limited, biased and heterogeneous data and missing investigation of long‐term effects. This evaluation demonstrates the lack of data, which prevents reliable conclusions on the safety of clonidine for long‐term sedation in critically ill children. For an evidence‐based use, further studies are needed.